Bahasa Jawa Dialek Brebes; Sebuah Telaah Fonologi Generatif - muhammad andi hakim (Faculty of Humanities, Universitas Jenderal Soedirman, 2016)
This research investigates the content of phonological variations of Bahasa Jawa Dialek Brebes. The analysis has been done in this study used generative phonology as an approach to analyze the problem of the research. The purpose of this study is to identify the sound’s variations of the language. The data of the study are dictionary and native speakers of the language. The method of this study is descriptive qualitative as the base rule of the process in analyzing the content of phonological rules in Bahasa Jawa Dialek Brebes. The results of the analysis show that the Bahasa Jawa Dialek Brebes contains with some phonological variation, such as assimilation, neutralization and syllable structure additiona